The Effect of Leg Muscle Training Using Rubber Bands on The Kinematic Parameters of Shooting Techniques in Female Soccer Athletes - Intan Anggraini; Tono Haryono; Iwa Ikhwan Hidayat (Universitas Negeri Semarang, 2025)
This study aims to analyze the effect of lower body exercises using rubber bands on the kinematic parameters of kicking technique in female soccer players. The method used is a single-group quasi-experimental design with pretest-posttest, involving 10 female soccer players from the Universitas Pendidikan Indonesia who participated in a six-week training program. This design is useful for determining the effect of rubber bands on the lower leg muscles after treatment. Kinematic data were analyzed using Skillspector 1.3, while kicking speed was tested using a paired sample t-test. The results showed an increase in several joint angles, particularly an increase in hip and ankle movement during the preparation and impact phases, as well as a more controlled and efficient follow-through pattern. Joint movements that changed angle a values indicated that treatment with rubber bands affected muscle reactions. An significant increase in kicking speed was also found, rising from 54.71 ± 6.86 km/h to 59.86 ± 8.63 km/h (p = 0.024), indicating increased strength and force transfer after training. These findings suggest that rubber band training effectively improves biomechanical efficiency and kicking speed, making it a recommended method for developing kicking skills and treating kicking injuries in female soccer players in Indonesia.